2021
DOI: 10.1002/cam4.4452
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated stroma reveals prognostic biomarkers and novel insights into the tumour microenvironment of colorectal cancer and colorectal liver metastases

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…In particular, distant metastases and postoperative relapses within 5 years after surgery in the group with a keloid-like collagen content of more than 30% were detected in 39.5% of patients, and in the group with a keloid-like collagen content of less than 30% in 15.5% of patients. These results are consistent with scientific research [ 32 34 ] and suggest a close relationship between keloid-like collagen and the metastatic behavior of cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, distant metastases and postoperative relapses within 5 years after surgery in the group with a keloid-like collagen content of more than 30% were detected in 39.5% of patients, and in the group with a keloid-like collagen content of less than 30% in 15.5% of patients. These results are consistent with scientific research [ 32 34 ] and suggest a close relationship between keloid-like collagen and the metastatic behavior of cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study suggested that another gene listed in our panel, NREP, was associated with poor prognosis and may be involved in the activation of cancer-associated fibroblasts and the epithelial-mesenchymal transition, with transforming growth factor β1 mediating both processes [61]. IGFBP7 was identified as a tumor stroma marker of epithelial cancers, and stromal expression of IGFBP7 was an indicator of poor survival in colorectal cancer [62,63]. When SW480 colorectal cancer cells were co-cultured with fibroblasts, IGFBP7 expression was induced in fibroblasts at both the mRNA and protein levels [64].…”
Section: Discussionmentioning
confidence: 88%
“…Levels of TGFBI in the liver correlate with the intensity of perisinusoidal fibrosis in Stab1 KO [33]. In cancer, stromal expression of POSTN is a predictor of poorer survival in CRC [34]. In tumor bearing, Stab1 deficient mice an accumulation of POSTN was predominantly seen in the matrix of Wt31 melanoma metastases (p = 0.0159).…”
Section: Discussionmentioning
confidence: 95%